Otomasi dan Optimasi Pengaturan Kerja pada Pondok Pesantren Menggunakan Profile Matching - Ardhi, Mokh Nugroho; Farazizah, Annisa Dinar; Firza, Fatmawati Hanifah; Yaqin, Muhammad Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Islamic boarding schools are religious institutions that provide education and teaching and develop and spread Islam. As an institution, Islamic boarding schools have many activities in them. In each activity requires an organizational structure to manage activities so that they are carried out properly. The process of selecting the person in charge is generally directly chosen by the board but this has both positive and negative sides. The positive side shortens the time in the election because there is no selection in determining the person responsible. The negative side of the direct appointment process is that it cannot see the abilities possessed by the candidates in charge of leadership, organization, and so on. This can only be known with the selection process, what often happens is the selection of the person in charge who does not have the appropriate ability. Under these circumstances, we need a system that can help boarding school administrators in facilitating the selection and appointment of the person in charge. In this study, profile matching is used to calculate the compatibility of the profile of the work and the profile of the person in charge. Each person in charge who is sought has each criterion consisting of core factors and secondary factors. The results obtained from this study are decision support systems that produce responsible recommendations in accordance with the criteria for each activity in the boarding school.